Moving images, moving subjects: representing selves and others between writing and photography - Gloudemans, Rachelle (Incontri. Rivista europea di studi italiani, 2020)
Review of: Giorgia Alù, Journeys Exposed: Women’s Writing, Photography and Mobility, New York & London, Routledge, 2018, 220 p., ISBN: 9781138345027, £120.00; ebook: 9780429437700 € 66,99.